Globalism, regionalism and nationalism : Asia in search of its role in the 21st century / edited by Yoshinobu Yamamoto. - Yamamoto, Yoshinobu. (Blackwell, 1999)
"Bringing together contributions from leading Asian. North American and European scholars, this book offers new insights into globalization, regionalism and nationalism and into Asian perspectives on international affairs."--BOOK JACKET.